PSEUDOMONAS AERUGINOSA: UNCOMMON CAUSE OF BACTERIAL MENINGITIS (Iraqi Journal of Medical Sciences, 2016)
Introduction:Gram negative bacillary meningitis is uncommon disease that needs proper diagnosis and urgent treatment to avoid serious complications. Escherichia coli, Klebsiella pneumonia and Pseudomonas aeruginosa are the most frequent gram negative bacilli. Use of third generation cephalosporins has made a significant therapeutic change with significant reduction in mortality. Ceftriaxone should always be the drug of choice until the full sensitivity report is available. Here, we report a case of bacterial meningitis caused by Pseudomonas aeruginosa which is thought to be secondary to previous ear infections. The diagnosis was confirmed by gram stain and culture of the cerebrospinal fluid. The patient was successfully treated with intravenous antibiotic for total of three weeks.Key words: Pseduomonas aeruginosa, meningitis, ear, infection.
Keywords: Pseduomonas aeruginosa; meningitis; ear; infection